Soil texture influences soil bacterial biomass in the permafrost-affected alpine desert of the Tibetan plateau - Shao, Ming; Zhang, Shengyin; Niu, Bin; Pei, Yu; Song, Sen; Lei, Tianzhu; Yun, Hanbo (Frontiers in Microbiology, 2022)
In a warming climate, permafrost thawing results in the release of Substantial carbon (C) into the atmosphere and potentially triggers strong positive feedback to global warming. Soil microorganisms play an important role in decomposing permafrost organic carbon, thus could regulate ecosystem C balance in permafrost regions. Soil microbial community and biomass are mainly determined by soil organic carbon (SOC) and soil texture. However, most studies focused on acid permafrost soil region (pH < 7), and very few related to alkaline permafrost-affected soil. Here we analyzed soil microbial community and biomass in the alpine desert and alpine steppe on Tibetan Plateau, where soil pH was around 8.7 ± 0.2 and 8.5 ± 0.1, respectively. Our results showed that microbial biomass was significantly correlated with main grain size (MGS) and SOC in the alkaline permafrost-affected soil (p < 0.05). Especially, bacterial and fungal biomasses were determined by SOC in the alpine steppe, whereas bacterial biomass was mainly affected by MGS and fungal biomass was determined by SOC in the alpine desert. Combined with the results of SEM, it suggested that soil microbial biomass was indirectly determined by soil texture, which through SOC content under high pH-value (pH 8-9). Plagioclase dominates soil texture in alpine steppe and alpine desert, which provide colonization sites for bacterial communities. This study highlights the importance of soil texture in managing soil microbial biomass and demonstrates the differential impacts of soil texture on fungal and bacterial communities in alkaline permafrost regions.